Controlling Seismic Excitation in the RCC Building with a Tuned Mass Damper. Issue 1 (November 2021) - Kalamkar, Avinash; Pitale, N.H.; Patil, P.B.
Abstract: The use of multiple tuned mass dampers (MTMDs) to monitor earthquake response of tall buildings is investigated. The MTMDs are located in three locations in the reinforced concrete (RC) structures. The time domain seismic analysis is performed on Etabs Software using imperial Earth movement used to analyze contemporary history. The performance of the MTMDs is compared to that of a TMD on the top floor, a TMD on the third and fifth floors, a TMD on each floor, and no TMD. The base shear vs time and displacement parameters were examined, and it was determined that the MTMDs on each floor are better for the building's seismic response. Furthermore, it has been discovered that MTMDs are more powerful than STMDs.